Colorectal Cancer Surveillance after Index Colonoscopy: Guidance from the Canadian Association of Gastroenterology. (2013) - Leddin, Desmond; Enns, Robert; Hilsden, Robert; Fallone, Carlo A; Rabeneck, Linda; Sadowski, Daniel C; Singh, Harminder
Abstract : BACKGROUND: Differences between American (United States [US]) and European guidelines for colonoscopy surveillance may create confusion for the practicing clinician. Under- or overutilization of surveillance colonoscopy can impact patient care. METHODS: The Canadian Association of Gastroenterology (CAG) convened a working group (CAG-WG) to review available guidelines and provide unified guidance to Canadian clinicians regarding appropriate follow-up for colorectal cancer (CRC) surveillance after index colonoscopy. A literature search was conducted for relevant data that postdated the published guidelines. RESULTS: The CAG-WG chose the 2012 US Multi-Society Task Force (MSTF) on Colorectal Cancer to serve as the basis for the Canadian position, primarily because the US approach was the simplest and comprehensively addressed the issue of serrated polyps. Aspects of other guidelines were incorporated where relevant. The CAG-WG recommendations differed from the US MSTF guidelines in three main areas: patients with negative index colonoscopy should be followed-up at 10 years using any of the appropriate screening tests, including colonos-copy, for average-risk individuals; among patients with >10 adenomas, a one-year interval for subsequent colonoscopy is recommended; and for long-term follow-up, patients with low-risk adenomas on both the index and first follow-up procedures can undergo second follow-up colonos-copy at an interval of five to 10 years. DISCUSSION: The CAG-WG adapted the US MSTF guidelines for colonoscopy surveillance to the Canadian health care environment with a few modifications. It is anticipated that the present article will provide unified guidance that will enhance physician acceptance and encourage appropriate utilization of recommended surveillance intervals.